Budaya Belajar dan Motivasi Berprestasi Siswa Belajar IPS di Kelas V UPT SDF Negeri Kakatua Kecamatan Mariso Kota Makassar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The main problem in this study is how culture encourages achievement motivation of students studying Social Sciences and how the form of achievement motivation of students learning Social Sciences in class V UPT SDF Negeri Kakatua. This study aims to find out the form of learning in encouraging student achievement motivation in social studies and to find out the form of achievement motivation of fifth grade students at UPT SDF Negeri Kakatua.This type of research is qualitative research and uses a qualitative descriptive approach. The subjects in this study were 2 class teachers and 5 students of class V UPT SDF Negeri Kakatua. Data collection techniques using: observation, interviews, and documentation. While the validity of the data in this study uses source triangulation.The results of the study show that: (1) the student learning culture has been implemented by the teacher who teaches in the class (2) student achievement motivation is important in achieving learning achievement The teacher's role is very important to improve student achievement by providing achievement motivation.Based on the results of the research above, it can be concluded (1) Student learning culture is something that needs to be implemented by teachers and carried out by students to support student behavior at school and outside school (2) achievement motivation needs to be given to students to support student achievement and student learning outcomes .